EFFECTS OF MULTICHANNEL RETAILING TOWARDS PURCHASE INTENTION OF HOUSEHOLD TEXTILES - Nugraha, Andre; Chaerudin, Rendra (Journal of Business and Management, 2018)
Abstract. Retail business has changed drastically in the past decade due to the latest development of information and communication technology and emerging online market. In general, consumers have respond enthusiastically with online retail continues to grow significantly for the past 20 years. Multi-channel retailing is seen as the way to go for retail businesses. The author intends to study what characteristic of multi-channel retailing that influences the consumer’s purchase intention towards household furniture textile products and how the characteristic of multi-channel retailing influences consumer’s retail decision to purchase household furniture textile products. The research is implemented within the scope of 95% confidence level, 7% precision interval, focus on household furniture textile, and respondents of Indonesian origin, 21-60 years old, and living in West Java and DKI Jakarta. The data analysis shows that characteristics of multichannel retailing does influence purchase intention and retail decision for respondents with varying effects based on demographic groups.Keywords: purchase intention, multichannel retailing, furniture textile, online retail, offline retail